Sie sind auf Seite 1von 13

Analytical and Graphical Convolution

Asif Hanif, Junaid Maqbool


{msee18003, msee18005}@itu.edu.pk

October 15, 2019

Analytical Convolution

For analytical convolution, we must have expressions for two signals. If you
are given graphs, you must express them mathematically to perform analytical
convolution.

Convolution is defined as:


Z +∞
y(t) = x(t) ∗ h(t) = x(τ )h(t − τ )dτ (1)
−∞

English translation:
Convolution of two signals x(t) and h(t) means finding area under a function
that is obtained by multiplying x(τ ) and h(t − τ ). Area under a function can
be found by integrating it within some desired limits.

Following are the two signals that we want to convolve;

x(t) = 2[u(t) − u(t − 1)]

h(t) = 2r(t) − 4r(t − 1) + 2r(t − 2)

Z +∞
y(t) = x(t) ∗ h(t) = h(t) ∗ x(t) = h(τ )x(t − τ )dτ (2)
−∞

1
Figure 1: Waveforms of two signals x(t) and h(t) against time axis.

In this example, it seems easier to keep h(t) at its place and flip+shift1 x(t).
By analyzing above equation, we see that two signals are needed to perform
convolution; h(τ ) and x(t − τ ). It is very straight forward to get expressions of
these two signals;

• Replace t with τ in h(t) to get h(τ )


• Replace t with t − τ in x(t) to get x(t − τ )

h(τ ) = 2r(τ ) − 4r(τ − 1) + 2r(τ − 2)


x(t − τ ) = 2[u(t − τ ) − u(t − τ − 1)]

Refer to Eq.2. We need to multiply h(τ ) and x(t − τ ) before integration. There-
fore, multiply expressions of h(τ ) and x(t − τ ) to move forward.

h(τ ) x(t − τ ) = [ 2r(τ ) − 4r(τ − 1) + 2r(τ − 2) ] [ 2[u(t − τ ) − u(t − τ − 1)] ]


= [ 2r(τ ) − 4r(τ − 1) + 2r(τ − 2) ] [ 2u(t − τ ) − 2u(t − τ − 1) ]
= [ 4r(τ )u(t − τ ) − 4r(τ )u(t − τ − 1)−
8r(τ − 1)u(t − τ ) + 8r(τ − 1)u(t − τ − 1)+
4r(τ − 2)u(t − τ ) − 4r(τ − 2)u(t − τ − 1) ]
1 Flipping is done AROUND y-axis and shifting is done ALONG x-axis.

2
We get 6 terms after multiplication. Again refer to Eq.2 and observe that we
have to integrate h(τ )x(t − τ ) over variable τ and for some shift t. Lets plug
expanded expression of h(τ )x(t − τ ) in Eq.2.

Z +∞
y(t) = h(τ )x(t − τ )dτ
−∞

Z +∞
= [ 4r(τ )u(t − τ ) − 4r(τ )u(t − τ − 1)−
−∞
8r(τ − 1)u(t − τ ) + 8r(τ − 1)u(t − τ − 1)+
4r(τ − 2)u(t − τ ) − 4r(τ − 2)u(t − τ − 1) ] dτ

Z +∞ Z +∞
= 4r(τ )u(t − τ )dτ − 4r(τ )u(t − τ − 1)dτ −
−∞ −∞
Z +∞ Z +∞
8r(τ − 1)u(t − τ )dτ + 8r(τ − 1)u(t − τ − 1)dτ +
−∞ −∞
Z +∞ Z +∞
4r(τ − 2)u(t − τ )dτ − 4r(τ − 2)u(t − τ − 1)dτ
−∞ −∞

Solving 6 integral seems a daunting task but fortunately we can exploit prop-
erties of convolution to make this task easy. Essentially, we need to solve only
one integral and answers of the rest of 5 integrals can be obtained by applying
convolution property on the first one.

Lets solve first integral;

Z +∞ Z +∞
4r(τ )u(t − τ )dτ = 4[ τ u(τ ) ]u(t − τ )dτ
−∞ −∞

It should not be difficult to write r(τ ) in terms of linear function and unit step.
Now comes the critical part: identifying the limits of integral. First observe
that u(τ ) remains zero for (τ < 0) and one for (τ ≥ 0). Secondly, u(t − τ ) or
u(−(τ − t)) remains zero for (τ > t) and one for (τ ≤ t). Therefore, in single
line, limits of τ for non-zero product of two unit step functions are 0 ≤ τ ≤ t.
In your mind, you may want to figure out question marks on the left
and right sides of τ such that function inside the integral remains
non-zero i.e (? ≤ τ ≤ ?) . Plots of u(τ ) and u(−(τ − t)) may also help you
visualize the limits in which product of these signals remains one.

3
Main Point:
We need to identify limits of τ in which function inside convolution
integral remains non-zero.

Z +∞
4r(τ )u(t − τ )dτ
−∞
Z +∞
= 4[ τ u(τ ) ]u(t − τ )dτ
−∞

If t > 0 , we can re-write the above integral as following


Z 0 Z t Z +∞
= 4[ τ u(τ ) ]u(t − τ )dτ + 4[ τ u(τ ) ]u(t − τ )dτ + 4[ τ u(τ ) ]u(t − τ )dτ
−∞ 0 t
Z t
=0+ 4[ τ × 1 × 1 ] dτ + 0
0
Z t
= 4[ τ ] dτ
0
t2
=4
2
= 2t2

Have you noted something


R +∞ in boxed statement? We use condition that if t > 0
then we get answer of −∞ 4r(τ )u(t − τ )dτ as 2t2 otherwise it is zero. It means
this answer is only valid for t > 0. Therefore, we can re-write this sentence in
the language of mathematics using two following ways;

Z +∞
4r(τ )u(t − τ )dτ = 2t2 for t > 0
−∞

OR
Z +∞
4r(τ )u(t − τ )dτ = 2t2 u(t)
−∞

Just image a case in which t < 0 and visualize plot of function inside convolution
integral. Comprehending the essence of this case will bolster your command on
convolution.

4
We are have figured out how to solve first convolution integral. By having look
on other convolution integrals, we understand that they can be represented by
some manipulation of first integral.

First Integral;
Z +∞
4r(τ )u(t − τ )dτ = 4 r(t) ∗ u(t) = 2t2 u(t)
−∞

Second Integral;
Z +∞
4r(τ )u(t − τ − 1)dτ = 4 r(t) ∗ u(t − 1) = 2(t − 1)2 u(t − 1)
−∞

Third Integral;
Z +∞
8r(τ − 1)u(t − τ )dτ = 8 r(t − 1) ∗ u(t) = 4(t − 1)2 u(t − 1)
−∞

Fourth Integral;
Z +∞
8r(τ − 1)u(t − τ − 1)dτ = 8 r(t − 1) ∗ u(t − 1) = 4(t − 2)2 u(t − 2)
−∞

Fifth Integral;
Z +∞
4r(τ − 2)u(t − τ )dτ = 4 r(t − 2) ∗ u(t) = 2(t − 2)2 u(t − 2)
−∞

5
Sixth Integral;
Z +∞
4r(τ − 2)u(t − τ − 1)dτ = 4 r(t − 2) ∗ u(t − 1) = 2(t − 3)2 u(t − 3)
−∞

We have obtained results of six integrals. Now, we can get final expression for
y(t).

y(t) = 2t2 u(t)−2(t−1)2 u(t−1)−4(t−1)2 u(t−1)+4(t−2)2 u(t−2)+2(t−2)2 u(t−2)−2(t−3)2 u(t−3)

= 2t2 u(t) − 6(t − 1)2 u(t − 1) + 6(t − 2)2 u(t − 2) − 2(t − 3)2 u(t − 3)

y(t) = 2t2 u(t) − 6(t − 1)2 u(t − 1) + 6(t − 2)2 u(t − 2) − 2(t − 3)2 u(t − 3)

Graphical Convolution

Now, we will convolve x(t) and h(t) using graphical method. By the end of this
section, you would appreciate graphical convolution method. However, you are
encouraged to perform convolution using these two methods just to make your
understanding clear.

In previous section, we learned that analytical convolution requires us to repre-


sent signals using ‘single-line’ precise mathematical expressions. In graphical
method, we still need mathematical expressions but you can define them piece
wise. For example x(t) = (some expression) for (t ≤ some constant).

Goal: Fill the graph of y(t) against time t where y(t) = x(t) ∗ h(t)

Step - 1: Plot x(t) and h(t) on t-axis


Step - 2: Plot x(τ ) and h(τ ) on τ -axis

6
Step - 3: Decide which function to flip+shift and which function to keep in-
tact on τ -axis. I choose x(τ ) for flipping and shifting. You will introduce an
arbitrary shift of value “t”. We are still on τ -axis. Here “t” is just some value
that is decided by you.
Step - 4: After flipping+shifting, you will get x(t − τ ). Imagine different values
of ”t” and plot x(τ ) on τ -axis. I would recommend you to start value of ”t”
from −∞ and gradually move towards +∞.
Step - 5: Once you have imagined value of “t”, plotted h(τ ) and x(t − τ ), then
point-wise multiply them and plot the product.
Step - 6: Integrate the function that was obtained after multiplication. Get
answer of integration.
Step - 7: Since, you obtained the answer of integration for a particular value
of “t”, therefore, place this answer on y-axis of y(t) graph at time=t.
Step - 8: Repeat Step-5 to Step-7 until entire time-axis or t-axis of y(t) is
filled.

Figure 2: Going from t-axis to τ -axis. Notice change in the expression of h(τ )

7
Figure 3: Going from t-axis to τ -axis. Notice change in the expression of x(τ )

Figure 4: Flipping x(τ ) on τ -axis

8
Figure 5: Shifting x(−τ ) by some shift t on τ -axis. x(t−τ ) = x(−(τ −t)). Values
of shift “t” are decided by you. I usually call right end of x(t − τ ) as “Head” and
left end as “Tail”. In this case, “Head” is “t” and “Tail” is “(−1 + t)”. Reins of
“Head” are in your hands and by sliding it on τ -axis “Tail” would follow you.
Keep in mind that by sliding “Head” on τ -axis does not change the width of
function. Sliding just changes the location of function on τ -axis.

In Step-4, you were asked to imagine different values of shift “t”. Following are
the cases in which different values or ranges of “t” are imagined.

Case - 0 : When (t < 0)

Figure 6: Case-0
Left: h(τ ) and x(t − τ ) , Right: Product of h(τ ) and x(t − τ )
If t ≤ 0, product of h(τ ) and x(t − τ ) will remain all over τ -axis. Hence, we get
zero after integration.

9
Z +∞
y(t) = (0) dτ
−∞
=0

Remember, in convolution, we integrate product of h(τ ) and x(t − τ ).

Case - I : When (0 ≤ t ≤ 1)

Figure 7: Case-I
Left: h(τ ) and x(t − τ ) , Right: Product of h(τ ) and x(t − τ )
If 0 ≤ t ≤ 1, product of h(τ ) and x(t − τ ) will remain non-zero from 0 to t over
τ -axis.

Z t
y(t) = (2 × 2τ ) dτ
0
= 2t2

English statement:
y(t) = 2t2 when (0 ≤ t ≤ 1)
Precise Mathematical Statement:
y(t) = 2t2 [ u(t) − u(t − 1) ]
Both statements are equivalent.

Case - II : When (1 ≤ t ≤ 2)

10
Figure 8: Case-II
Left: h(τ ) and x(t − τ ) , Right: Product of h(τ ) and x(t − τ )
If 1 ≤ t ≤ 2, product of h(τ ) and x(t − τ ) will remain non-zero from (−1 + t) to
t over τ -axis.

Z 1 Z t
y(t) = (2 × 2τ ) dτ + (2 × −2(τ − 2)) dτ
−1+t 1
= −4t2 + 12t − 6

English statement:
y(t) = −4t2 + 12t − 6 when (1 ≤ t ≤ 2)
Precise Mathematical Statement:
y(t) = (−4t2 + 12t − 6) [ u(t − 1) − u(t − 2) ]

Case - III : When [1 ≤ (−1 + t) ≤ 2] ⇒ (2 ≤ t ≤ 3)

Z 2
y(t) = (2 × −2(τ − 2)) dτ
−1+t
2
= 2t − 12t + 18

11
Figure 9: Case-III
Left: h(τ ) and x(t − τ ) , Right: Product of h(τ ) and x(t − τ )
If 2 ≤ t ≤ 3, product of h(τ ) and x(t − τ ) will remain non-zero from (−1 + t) to
2 over τ -axis.

English statement:
y(t) = 2t2 − 12t + 18 when (2 ≤ t ≤ 3)
Precise Mathematical Statement:
y(t) = (2t2 − 12t + 18) [ u(t − 2) − u(t − 3) ]

Case - IV : When [(−1 + t) ≥ 3] ⇒ (t ≥ 4)

Figure 10: Case-IV


Left: h(τ ) and x(t − τ ) , Right: Product of h(τ ) and x(t − τ )
If t ≥ 4, product of h(τ ) and x(t − τ ) will remain zero over entire τ -axis.

Z +∞
y(t) = (0) dτ
−∞
=0

You are being reminded again that in convolution, we integrate h(τ ) and x(t−τ )

12
Now we can combine precise mathematical statements together to get final ex-
pression of y(t).

y(t) = 2t2 [ u(t) − u(t − 1) ]+


(−4t2 + 12t − 6) [ u(t − 1) − u(t − 2) ]+
(2t2 − 12t + 18) [ u(t − 2) − u(t − 3) ]
= 2t2 u(t) + (−6t2 + 12t − 6) u(t − 1) + (6t2 − 24t + 24) u(t − 2) − (2t2 − 12t + 18) u(t − 3)
= 2t2 u(t) − 6(t2 − 2t + 1) u(t − 1) + 6(t2 − 4t + 4) u(t − 2) − 2(t2 − 6t + 9) u(t − 3)
= 2t2 u(t) − 6(t − 1)2 u(t − 1) + 6(t − 2)2 u(t − 2) − 2(t − 3)2 u(t − 3)

y(t) = 2t2 u(t) − 6(t − 1)2 u(t − 1) + 6(t − 2)2 u(t − 2) − 2(t − 3)2 u(t − 3)

This answer exactly matches with the one we obtained using analytical convo-
lution.

Following are the Desmos hyper-links to interactively play with signals;

• Step-1

• Step-2
• Step-3
• Step-4

We hope this example would have provided good understanding of convolution.


Do provide us feedback for any improvement in this document. Your feedback
helps us understand how to convey message more effectively.

13

Das könnte Ihnen auch gefallen